Historical and Current Diversity Patterns of Mediterranean Marine Species - Lo Brutto, Sabrina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Mediterranean Sea is a semi-enclosed basin which experienced different natural and anthropogenic phenomena causes of community or intra-species changes over time. The Mediterranean Sea went through dramatic changes in its biota through the last 6 million years and more quickly in the recent century. All the events left a footprint on the gene pool of marine species, on their morpho-anatomical features, and on the loss or expansion of the geographical range extent. Nowadays the Mediterranean basin is changing its physical and ecological characteristics. The changes in its environmental conditions are followed by changes in its species composition and have been recorded in historical museum collections. In this book, the biodiversity in the Mediterranean Sea is described at a synchronic or diachronic level, highlighting the past two centuries for which museum collections can provide overlooked information.